Steganografi Video Menggunakan Metode End Of File dan Metode Caesar Chiperext - Darmawati, Darmawati; Basri, Muh. (Jurnal Sintaks Logika, 2024)
the application of technology in the field of data and information security has been widely implemented. Threats to information security can occur when the information sent is not addressed to everyone but only to cartain people, especially if the information provided is confidential. The aim of this research is to develop software that can hide cinfidential information on media. The method used is end of file in the encryption process, and to insert text into the video using the caesar chipertext method, using the php programming language. Based on the test carried out, an application was produced than can be used toh ide information using video. The result of this research are changes in the size of the video namely the size of the original video compered to the size of the video after being inserted has increased